A Visualisation Technique to Communicate Implicit Feedback Decisions - White, Ryen W. (26th Annual European Conference on Information Retrieval (ECIR 2004) Sunderland, United Kingdom, 2004)
This poster describes a visualisation technique for communicating the effects of implicit feedback decisions using a familiar interface component, the scrollbar. The results of a pilot evaluation show the technique is unobtrusive and encourages focused interaction.